Possible relationship between certolizumab pegol and arrhythmias: report of two cases - R. Talotta; F. Atzeni; A. Batticciotto; D. Ventura; P. Sarzi-Puttini (PAGEPress Publications, 2016)
It is still unknown whether there is an association between the use of certolizumab pegol (CZP) in rheumatic patients and the onset of cardiac arrhythmias. We describe the cases of two patients with rheumatoid arthritis (RA) treated with CZP as the first-line biological drug and methotrexate (MTX), who developed an arrhythmic event. The first was a 60-year-old, hypertensive male smoker, the second a 66-year-old dyslipidemic female non-smoker. Both were diagnosed as having RA in 2010, and started treatment with MTX plus CZP. The first patient developed undatable atrial fibrillation, which was resistant to pharmacological treatment and electrical cardioversion. The second patient developed an atrial flutter, which was treated with a betablocker. In both cases, we set a cautious interval between two consecutive administrations of CZP and, in the first case, also reduced the dose of MTX without any worsening of RA activity. Although many studies have shown that tumor necrosis factor (TNF)-alpha plays a pathogenetic role in inducing an arrhythmogenic substrate that is apparently rescued by anti-TNF drugs, there is still a lack of conclusive data. We suggest caution in any patient developing a cardiac event (including rhythm disorders) during treatment with a conventional or biological disease-modifying anti-rheumatic drug.